Od teatru do telewizji i internetu. Rzecz o Teatrze Telewizji - Rudzińska, Agata (Postscriptum Polonistyczne, 2020)
Television Theatre is a specific genre that is a characteristic unique to Polish media. It began with the creation of TV. In the beginning it aimed only at transferring traditional theatrical shows into a new medium. It became very popular with live transmissions of theatrical shows from TV studios. Later it adopted new technical and staging possibilities. It has evolved over the years, creating different styles and tendencies, due to the development of television itself and the achievements of the theoreticians as well as people involved in theatrical productions. Lately it has also turned to the Internet and because of that a mass audience has gained access to a high art form.